Performance Comparison of Resistance Temperature Detector and Liquid Filled Thermometer on Turbine Guide Bearing at Siguragura HPP. - Prayitno, Fajar Nur; Rahmaniar, Rahmaniar; Anisah, Siti (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
The Turbine Guide Bearing (TGB) is a critical component at the Siguragura Hydroelectric Power Plant (HPP), responsible for ensuring the turbine shaft rotates on its axis, allowing the turbine to operate efficiently without excessive heat buildup that could lead to failure. This requires continuous temperature monitoring of the Turbine Guide Bearing. The temperature sensors used for this monitoring are the Resistance Temperature Detector (RTD) and the Liquid Filled Thermometer. These two sensors operate based on different mechanisms, making it essential to analyze their performance to ensure compatibility and maintain the accuracy and reliability of temperature measurements. Based on calibration and field testing results, the RTD sensor demonstrated more accurate and stable temperature readings, with a minimal deviation from the standard and linear, non-fluctuating results. On the other hand, the Liquid Filled Thermometer was more responsive, with a faster response time to reach the reference temperature. Therefore, the most suitable sensor for measuring the temperature of the Turbine Guide Bearing at Siguragura HPP is the RTD as the primary sensor, while the Liquid Filled Thermometer can serve as a redundant sensor.